Depression in the Elderly: Risk Assessment and Prevention - Srijai, Kridanai; Wongsawat, Pramote (Journal of Phrapokklao Nursing College, Chanthaburi, 2024)
Depression is a common mood disorder that affects the mind. It affects daily life, loss of function in various domains, and leads to a higher risk of death from suicide. The depression problem in the elderly is increasing according to the trend of the aging society. This is a problem that people who are involved, especially those who are close or responsible for caring for the elderly, may provide care immediately before the elderly develops depression, by observing emotional symptoms such as sadness, boredom, disillusionment, hopelessness, worthlessness, and decreased interest in things together with observing behavioral symptoms such as insomnia or oversleeping, sleepy, lose their appetite or overeating, slow or increased movement, restlessness, lack of strength, and fatigue. If such symptoms are found, the elderly can be assessed the risk of depression by a 2-question depression screening (2Q). If it is found to be at risk of depression, they will be referred for further depression assessment by healthcare professionals following the guidelines of the Department of Mental Health. Although the assessment results showed no depression, this will help the elderly at risk can raise awareness individuals and those who are responsible for caring for the elderly provide care for preventing depression and will help the elderly have a good quality of life.